Kan vi beregne hvor mange rein beitene tåler? - Gaare, Eldar (Rangifer, 1999)
Can we calculate how many reindeeer the pastures allow for? Three methods have been used to keep the reindeer population in accordance with the pasture resources. The carrying capacity is found by: 1) looking at the growth and well being of the animal (That is the "good old" way) 2) comparing unknown reindeer areas with well pracatised areas (Reindeer pasture convention of 1965) 3) estimating the yearly growth of lichens that can be grazed (Wild Reindeer Management after 1965) An economical carrying capacity has to be found by systematical asessment of the condition of the animals and the herd’s production and at the same time value til condition of the pastures.